PENGARUH TEAMWORK TERHADAP KINERJA GURU SMP YAMAMA BANDAR LAMPUNG - Putri, Tasya Nabila; Patimah, Siti; Bedi, Fisman; Ayu, Sovia Mas (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
Armstrong and Baron's theory states that teacher performance can be influenced by individual factors (personal factors), leadership factors (leadership factors), group factors / colleagues / work teams (team factors), system factors (system factors), and situational factors (contextual / situational factors). Teamwork that is formed in general will certainly lead to performance. However, in the realm of education, it is not necessarily able to bring out good performance as expected. The purpose in writing this article is to examine more deeply the influence of teamwork on the performance of teaching staff at Yamama Lampung Junior High School. The method used in writing this scientific article uses quantitative research methods, using ex post facto techniques or models. The population in this study amounted to 55 people with sampling techniques using the Krejcie & Morgan formula or table and sampling around 43 respondents. The results obtained based on the data and research results show that there is a negative and insignificant influence between the work team on teacher performance at Yamama Lampung Junior High School. The teacher work team at Yamama Lampung Junior High School that has been formed looks good and solid, so it will not affect the high or low performance of teachers in carrying out their main duties.